Design, synthesis & biological evaluation of ferulic acid-based small molecule inhibitors against tumor-associated carbonic anhydrase IX. Issue 9 (1st May 2020) - Aneja, Babita; Queen, Aarfa; Khan, Parvez; Shamsi, Farheen; Hussain, Afzal; Hasan, Phool; Rizvi, M. Moshahid A.; Daniliuc, Constantin G.; Alajmi, Mohamed F.; Mohsin, Mohd.; Hassan, Md. Imtaiyaz; Abid, Mohammad
Graphical abstract: Abstract: Carbonic anhydrase IX (CAIX) is an emerging drug target for hypoxia associated cancers. To identify potent and selective inhibitors of CAIX, a small library of ferulic acid (FA) derivatives bearing triazole moiety has been designed, synthesized and evaluated against different human CA isoforms (CAII, CAVA & CAIX). Though most of the compounds showed CAIX inhibition in the micromolar range, compound 7i selectively inhibits CAIX in the nanomolar range (IC50  = 24 nM). In silico analysis revealed binding of 7i with the catalytically important amino acid residues of CAIX. Further, cell-based studies indicate that 7i inhibits the activity of CAIX, decreases the epithelial to mesenchymal transitions, induces apoptosis, inhibits cell migration and colonization potential of cancer cells. Taken together, these results emphasized the use of 7i as a prospective pharmacological lead molecule in CAIX targeted anticancer therapeutics.